Health and Academic Achievement 2018
DOI: 10.5772/intechopen.71842
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drugs on Cognitive Functions

Abstract: Disorders related to the misuse of certain drugs represent not only a worldwide public health problem, but also an economic and social issue. Adolescents and children represent the most vulnerable population for drug consumption and addiction. At this early stage in life, a crucial phase of the neurodevelopmental process, substance abuse can induce brain plasticity mechanisms that may produce long-lasting changes in neural circuitry and ultimately behavior. One of the consequences of these changes is the impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 102 publications
(114 reference statements)
0
9
0
3
Order By: Relevance
“…Alcohol alone has been reported to increase the desire to have sex and to initiate or participate in sex [ 22 - 24 ]. The use of intravenous drugs or other illicit substances has also been reported to increase cognitive inhibition [ 25 ] and poor behavioural judgment [ 26 ]. Several illicit drugs, such as opium, produce intense feelings of pleasure, which could directly stimulate feelings of sexual desire and pleasure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol alone has been reported to increase the desire to have sex and to initiate or participate in sex [ 22 - 24 ]. The use of intravenous drugs or other illicit substances has also been reported to increase cognitive inhibition [ 25 ] and poor behavioural judgment [ 26 ]. Several illicit drugs, such as opium, produce intense feelings of pleasure, which could directly stimulate feelings of sexual desire and pleasure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…47 There has been a growing body of evidence which points towards neurocognitive decline due to drug misuse. [48][49][50] Social drug misuse frequently involves drug takers in various risktaking behaviors. 51 Some studies have shown that low to moderate alcohol consumption may facilitate cognition;- 52,53 others have shown that it impairs cognition 54 or produces no change.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than a regular daily pattern of chronic MP administration, healthy individuals may consume MP only during peak periods when its cognitive-enhancing effects are desired (Beyer, Staunton, & Moodley, 2014;Franke, Lieb, & Hildt, 2012;Juárez-Portilla, Molina-Jiménez, Morin, Roldán-Roldán, & Zepeda, 2018;Urban & Gao, 2017). These patterns of use are also evident in individuals with ADHD who are prescribed MP.…”
Section: Introductionmentioning
confidence: 99%